Misconception Tool: Web-Based Assessment of Buoyancy Materials - Maison; Hidayat, M.; Kurniawan, Dwi Agus; Sandra, Rizka Octavia; Yolviansyah, Fauziah; Iqbal, Muhammad (Universitas Pendidikan Ganesha, 2022)
Currently, the measurement and assessment process that uses paper is considered less effective and less efficient because it is relatively difficult to score, takes longer, and does not save paper. Therefore, web-based assessment is a better choice in some instances and conditions. The purpose of this study was to develop a web-based assessment that will be used to identify students' misconceptions about the buoyant material. This research is development research (R&D) using the ADDIE model, which involved two validators, a teacher, and 20 students, as respondents in the development process. Data collection was carried out using instruments and interviews. The implication in this study is to be able to identify the occurrence of misconceptions experienced by students by involving technology in conducting assessments carried out by teachers. The data obtained were analyzed using descriptive statistics and Miles and Huberman analysis. The study results indicate that in the use of web-based assessment, students get an average percentage of misconceptions <20%, which is included in the SR category (very low). User response to this web-based instrument is good, so it is feasible. With this, it can be said that it is necessary to apply web-based assessment in the process of tests and assessments in schools.